Alternatives for the location of USW sorting stations in the Province of Misiones: clusterization by k-means, application of weighted factors and analytical hierarchy for decision-making (AACINI - International Journal of Industrial Engineering, 2023)
The objective of this work is to evaluate the alternatives for the location of urban solid waste (USW) classification stations in the province of Misiones. To do this, firstly, the number of alternatives to be evaluated is determined by means of the “k-means” clustering method. Then, in order to prioritize the alternatives given by k-means and determine the best locations, the methods of weighted factors and analytical hierarchy are applied, the latter also known as AHP (Analytic Hierarchy Process). The variables evaluated in the prioritization of alternatives include the population density for each department of the province, ease of installation of the station, amount of waste produced and geographic location (proximity to the provincial route and far from the city).
Keywords: USW; localization; classification stations; clustering; alternatives